Burden of dental diseases in India as compared to South Asia: An insight - S M Balaji (Wolters Kluwer Medknow Publications, 2018)
Introduction: In the recent past, the level of prevalence and incidence of dental caries and periodontal diseases in India and its comparison with South-Asian neighbors have not been reported. The manuscript estimates the same using the global disease burden 2016 approach. Materials and Methods: Secondary data analysis of primary data presented by Vos et al., 2016, was used for this study. Data from the global burden of disease, data at https://vizhub.healthdata.org/gbd-compare/and http://ghdx.healthdata.org/gbd-results-tool, and data for permanent dental caries, periodontal diseases, and overall dental disorders for both genders (age standardized) at prevalence, incidence, and disability-adjusted life years (DALYs) were obtained for India and South Asian region and compared qualitatively. Results: For every 100,000 Indians, as compared to South Asian males (30,903 in every 100,000), Indian males (31,489) had prevalence of dental caries. Among females, the same was 33,926 for South Asians and 34,426 for Indians. Similarly, the 2016 incidence of dental caries was higher among Indians as compared to South Asians and more females suffered from dental caries than males, whereas a reversal of gender trend was observed with periodontal disease. Overall dental disorder burden from 1990 to 2016 is presented. Conclusion: There is a difference between genders in the prevalence, incidence, and DALYs of caries of permanent dentition and that of periodontal diseases. As compared to South Asia, India has more burden of dental diseases. Indian dental workforce and oral health policy need to be realigned to counter the burden of oral disorders.